Recurso extraordinário, recurso especial e o caráter vinculante dos precedentes oriundos de seu julgamento - Cury, Augusto Jorge (2019)
Masters dissertation consistent in scientific research that aims to addresses problems inherent to the binding effectiveness of the precedents derived from decisions of extraordinary appeal and special appeal, respectively, from Federal Supreme Court and Superior Court of Justice. Through deductive methodology, and with fulcrum in Brazilian legislation and in the lessons of the classical doctrine and of the current legal literature, this study concludes that, starting from the constitutional functions of these appeals, as well as based on the “supreme courts” nature of those courts, it’s imperative to recognize the obligation to comply with the judicial precedents derived from decisions of extraordinary appeal and special appeal, even when they aren’t subject to the multiple appeals regime. This conclusion, moreover, finds no obstacle in other constitutional provisions and also assists in the implementation of a series of constitutional principles established as fundamental rights